Endothelial Dysfunction in Heart Failure With Preserved Ejection Fraction: What are the Experimental Proofs? - Cornuault, Lauriane; Rouault, Paul; Duplàa, Cécile; Couffinhal, Thierry; Renault, Marie-Ange (Frontiers in Physiology, 2022)
Heart failure with preserved ejection fraction (HFpEF) has been recognized as the greatest single unmet need in cardiovascular medicine. Indeed, the morbi-mortality of HFpEF is high and as the population ages and the comorbidities increase, so considerably does the prevalence of HFpEF. However, HFpEF pathophysiology is still poorly understood and therapeutic targets are missing. An unifying, but untested, theory of the pathophysiology of HFpEF, proposed in 2013, suggests that cardiovascular risk factors lead to a systemic inflammation, which triggers endothelial cells (EC) and coronary microvascular dysfunction. This cardiac small vessel disease is proposed to be responsible for cardiac wall stiffening and diastolic dysfunction. This paradigm is based on the fact that microvascular dysfunction is highly prevalent in HFpEF patients. More specifically, HFpEF patients have been shown to have decreased cardiac microvascular density, systemic endothelial dysfunction and a lower mean coronary flow reserve. Importantly, impaired coronary microvascular function has been associated with the severity of HF. This review discusses evidence supporting the causal role of endothelial dysfunction in the pathophysiology of HFpEF in human and experimental models.